A self-immolative linker that releases thiols detects penicillin amidase and nitroreductase with high sensitivity via absorption spectroscopy. Issue 19 (16th February 2022) - Espinoza, Eli M.; Røise, Joachim J.; He, Maomao; Li, I-Che; Agatep, Alvin K.; Udenyi, Patrick; Han, Hesong; Jackson, Nicole; Kerr, D. Lucas; Chen, Dake; Stentzel, Michael R.; Ruan, Emily; et al.
Abstract : This article reports the synthesis and characterization of a novel self-immolative linker, based on thiocarbonates, which releases a free thiol upon activation via enzymes. Abstract : This article reports the synthesis and characterization of a novel self-immolative linker, based on thiocarbonates, which releases a free thiol upon activation via enzymes. We demonstrate that thiocarbonate self-immolative linkers can be used to detect the enzymes penicillin G amidase (PGA) and nitroreductase (NTR) with high sensitivity using absorption spectroscopy. Paired with modern thiol amplification technology, the detection of PGA and NTR were achieved at concentrations of 160 nM and 52 nM respectively. In addition, the PGA probe was shown to be compatible with both biological thiols and enzymes present in cell lysates.